2007
DOI: 10.1016/j.ejcnurse.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue is a Prevalent and Severe Symptom Associated with Uncertainty and Sense of Coherence in Patients with Chronic Heart Failure

Abstract: Although fatigue is a prevalent and distressing symptom in patients with chronic heart failure (CHF), it is an underestimated problem in the care of patients, and consequently, insuffi ciently investigated. The primary aim of this thesis was, therefore, to advance the knowledge from the patients' perspective by describing characteristics of the fatigue experience and its consequences in daily life in patients with CHF. A secondary aim was to investigate the relationships between fatigue and selected physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
100
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 107 publications
10
100
0
4
Order By: Relevance
“…Decreased motivation and interest in surroundings, an attribute of fatigue presented by Trendall [15], was not relevant for the women with CHF in our study, where the experience of fatigue seemed to be mostly of a physical character. This is in accordance with earlier findings among patients with CHF [5][6][7]. The role of age in this matter should not be disregarded.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased motivation and interest in surroundings, an attribute of fatigue presented by Trendall [15], was not relevant for the women with CHF in our study, where the experience of fatigue seemed to be mostly of a physical character. This is in accordance with earlier findings among patients with CHF [5][6][7]. The role of age in this matter should not be disregarded.…”
Section: Discussionsupporting
confidence: 93%
“…In the findings of the present study, dysfunction of daily life activities was observed, also in the study by Faulk, there was a significant relationship between fatigue and patient's reduced function (45). Fatigue is considered as a limiting factor for physical activity (19), while excessive fatigue leads to reduced skeletal muscle function (46), which occurs due to increased catabolic muscle myopathy, therefore reduced activity and fatigue accompany skeletal muscle inappropriate function (19,24,46).…”
Section: Discussionsupporting
confidence: 74%
“…In another comparative study, it was also clear that there is a significant relationship between fatigue factor, anxiety and depression (19). Different studies reported fatigue symptoms with depression signs in patients with heart failure (39,45) and coronary artery (52). Also in the study of Guallar-Castillon et al (53), 48.8% of heart failure patients had depression; the authors of this research believed that depression may prepare patients for other psychological factors and progresses the disease.…”
Section: Discussionmentioning
confidence: 66%
“…Fatigue is recognised as a prevalent and severe health problem in patients with chronic heart failure (CHF) [1,2]. Fatigue presents a number of serious threats to an individual's well-being, affecting both body and mind.…”
Section: Introductionmentioning
confidence: 99%